Risk Factor Analysis of Residential Topography and Age on Prostate Cancer Incidence - Nabilah, Aisyah; Kurniati, Yuni Prastyo (Faculty of Medicine, Universitas Jember, 2024)
Prostate cancer is malignancy that originates from the luminal and basal epithelial acinar of prostate gland. Global Cancer Statistics in 2020 stated that prostate cancer is the third most common type of cancer in the world. The incidence and mortality of prostate cancer in Indonesia ranks 10th out of 32 Asian countries. Prostate cancer is multifactorial disease influenced by genetic mutations and inflammation. Research shows risk factors include increasing age and topographical factors of residence. Literature studies from various sources related to age and topography of residence in prostate cancer are still very limited. This study aims to analyze the effect of topographic profile factors of rice fields around the residence and age on the severity of prostate cancer An Observational analytic study was conducted with a case control design. Total of 177 samples using total sampling method. Age variable parameters are less than or more than 65 years. While the topography of residence uses a cut-off point of 39%. The results of the chi-square test found a significant influence between topographic profile of rice fields around the residence with prostate cancer incidence (p = 0.028, OR = 2.155). The results also found a significant influence between age factor with prostate cancer incidence (p=0.018, OR=2.187). The incidence of prostate cancer caused by the topographic profile of residence and age amounted to 7.2%. In conclusion shows that the topographic profile of the rice field area around the residence and age have a significant influence on prostate cancer severity. Keywords: age, pollutant, prostate cancer, residence, rice field